Consumption effects of edible oils on the biochemical cardiovascular risks in hyperlipidemic rats - Abushal, Suzan A.; Alqahtani, Nashi K.; Abdulfattah, Ahmed M.; Abuzinadah, Mohammed F.; Izmirly, Abdullah M.; Sami, Rokayya; Zarah, Rowa K.; Hamdi, Hamida; Al-Sulami, Nadiah; Almasoudi, Suad H.; Albishi, Tasahil S.; Qari, Sameer H.; et al. (Frontiers in Sustainable Food Systems, 2025)
BackgroundThe growing prevalence of cardiac diseases has heightened the necessity to adjust modern lifestyles to achieve a better balance and diversification of the nutrients and oil consumption in the daily diet.MethodsThis study explored the impact of various edible oils (0.4 mL/100 g B. W./day) on the biochemical cardiovascular risks in hyperlipidemic rats (olive, coconut, palm, soybean, sunflower, and flaxseed) which coded as OLO, COO, PAO, SOO, SUO, and FLO groups, respectively. The study designed for 60 days, utilized male Sprague–Dawley rats weighing 330–350 g. The rats were divided into seven sections each containing eight rats. Rats were fed a high-fat diet for 21 days to induce hyperlipidemia. Several parameters were assessed, including body weight, glucose, insulin, lipid profile, and key metabolic indicators such as oxidative stress and inflammatory markers, as well as parameters related to the heart and kidneys.ResultsThe FLO and OLO groups presented a reduction in body weight of 21.70 g and 20.27 g, respectively. All cardiovascular risk markers and lipid profile values were improved by FLO consumption, except triglycerides (TG) (97.11 mg/dL) and low-density lipoprotein cholesterol (LDL-c) (55.12 mg/dL), which were improved by OLO consumption. FLO and OLO groups also have positive effects on glucose and insulin resistance levels (IRL) and inflammatory cytokines. Rats in the PAO group reported the highest value of IRL, at 23.28 μU/mL, compared to the COL group, at 8.87 μU/mL. SUO group detected a lower value of TNF-α to the COL group at 37.42 pg./mL and 37.55 pg./mL, respectively. The heart cardiac hypertrophy (CH) index of 0.40 mg/dL was found to be the same for the COO, SOO, SUO, and FLO groups.ConclusionAccording to the results, extra experimental work is needed on PAO to find out the relationship between cardiovascular disease risk in the long run compared with the other edible oils. Administration of OLO, FLO, and SUO demonstrated protective activity against these factors.